Bacterial Contamination of Children’s Toys in Rural Day Care Centres and Households in South Africa - Ledwaba, Solanka Ellen (Int J Environ Res Public Health, 2019)
Background: Young children exhibit a high susceptibility to several diarrhoea-causing bacterial microorganisms. In this study, the prevalence of fecal contamination on children’s toys was determined using total coliform and E. coli as bacterial fecal indicators. The prevalence of diarrhoeagenic E. coli strains were used as an indication of the potential health risks. Materials and Methods: A cross-sectional descriptive study was carried out for 3 months in rural communities in the Vhembe district, Limpopo province of South Africa. Nonporous plastic toys (n = 137) used by children under 5 years of age in households and day care centres (DCCs) from rural villages were collected for assessment. New toys (n = 109) were provided to the households and DCCs and collected again after 4 weeks. Microbiological assessment was carried out using the Colilert(®) Quanti-Tray/2000 system. Diarrhoeagenic E. coli strains were identified using a published multiplex PCR protocol. Results: Water, sanitation and hygiene (WASH) conditions of the children in the households and DCCs were assessed. Statistical analysis was used to identify the relationship between fecal contamination of the existing and introduced toys. All the existing and introduced toy samples, both from DCCs and households, tested positive for total coliform counts and 61 existing and introduced toy samples tested positive for E. coli counts. Diarrhoeagenic E. coli strains identified included EHEC, ETEC, EPEC, EIEC and EAEC. Conclusions: The results indicated that water, sanitation and hygiene conditions could be responsible in the contamination of children’s toys and the transmission of diarrhoea to young children.